An optimized protocol for metabolic measurement in 3D tumor spheroids derived from primary and established glioblastoma cells - Samiya Al-Robaiy; Urszula Hohmann; Andreas Simm; Faramarz Dehghani; Julian Prell; Christian Strauss; Tim Hohmann (PLoS ONE, 2026)
Tumors are characterized by a multitude of genetic and epigenetic alterations, including a deregulation of the metabolism, driving migration and infiltration. To mimic the energetic landscape of in vivo tumors, 3D models surpass traditional 2D cultures, by introducing regions of different nutrient and oxygen supply. Yet, the analysis of metabolic processes in 3D cultures, including the mitochondrial answer and extracellular fluxes is more challenging. The extracellular flux analyzer is a powerful tool for investigating cellular metabolism, offering valuable insights that can drive advancements in biomedical research, but protocols for analysis of 3D cultures are sparse. Here, we present a protocol for optimized extracellular flux analysis, starting from the choice of the 3D culture model, dependencies on 3D culture size and testing multiple normalization approaches for two different glioblastoma and two primary cell lines. It was demonstrated that our approach was feasible for different glioblastoma cell lines, showing cell type and spheroid size dependent responses to metabolic challenges. In addition, normalization approaches using essentially 2D characteristics of spheroids were found insufficient to account for different spheroid sizes and cell lines. The data showed that using bio-printed spheroids with magnetic beads, combined with normalization to the median values of an experiment and the initially seeded cell number, delivered the most reliable results. Thus, we provided an approach that enables a straightforward and reproducible generation of 3D cell cultures and offer strategies to optimize metabolic measurements within these cultures.